2020
DOI: 10.3389/fpsyg.2020.597671
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism, Conspiracy Beliefs, Gender and COVID-19: Links Between Individual Differences and Concern About COVID-19, Mask Wearing Behaviors, and the Tendency to Blame China for the Virus

Abstract: The present study investigated variables potentially associated with a lack of concern about COVID-19 and belief in the conspiracy theory that China is responsible for the virus. In particular, the study looked at Authoritarianism, Conspiracy Beliefs, gender, and consistency of handedness as predictors of nine Likert-type items gauging attitudes, behavior, and beliefs regarding the virus. Initial analyses showed that Authoritarianism predicted less concern about the impact of the virus on health, less mask wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 18 publications
3
63
1
2
Order By: Relevance
“…Differences in associations between community mitigation policies and rapid riser identification by urbanicity might also reflect variability in awareness of and adherence to mitigation policies. Previous studies have shown differences in mask-wearing behavior and other mitigation behaviors by gender, age, ethnicity, and urbanicity 21 , 22 , 23 , 24 . Further, inherent differences in structural and social factors of counties could have influenced both statewide mitigation policies and individual behavior, and thus, may also have contributed to differences in observed associations by urbanicity [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 97%
“…Differences in associations between community mitigation policies and rapid riser identification by urbanicity might also reflect variability in awareness of and adherence to mitigation policies. Previous studies have shown differences in mask-wearing behavior and other mitigation behaviors by gender, age, ethnicity, and urbanicity 21 , 22 , 23 , 24 . Further, inherent differences in structural and social factors of counties could have influenced both statewide mitigation policies and individual behavior, and thus, may also have contributed to differences in observed associations by urbanicity [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 97%
“…The growing problem of conspiracy theory-driven noncooperation is worth noting in the present context (Arnot et al, 2020;Prichard and Christman, 2020). As an epiphenomenon of adaptive rationalization mechanisms, conspiratorial thinking may be triggered as people struggle to gain a sense of control during crises such as COVID-19 (Yong et al, 2020).…”
Section: The Emerging Role Of Conspiratorial Thinking In Noncooperatimentioning
confidence: 94%
“…The emotion of disgust has far-reaching implications for several areas of psychology, from cognition, judgment, decision-making, and social relationships to health and other behaviors ( Al-Shawaf et al, 2018 ), and so it may be reflected in the decisions that women make even at relatively high levels of abstraction when faced with a pathogenic threat. During the COVID-19 pandemic, women in the general public showed more concern about their own and others’ health ( Prichard and Christman, 2020 ), wearing masks 1.5× more frequently than men ( Haischer et al, 2020 ), even though COVID-19 disease severity and mortality are higher in men ( Krams et al, 2020 ). These sex differences extend even to dreams during the COVID-19 pandemic: a cross-national study on 1,998 women and 890 men reported that women showed significantly lower positive emotions in their dreams and higher rates of negative emotions, anxiety, sadness, anger, body content, and references to biological processes, health, and death than men ( Barrett, 2020 ).…”
Section: Psychobehavioral Sex Differencesmentioning
confidence: 99%
“…Women also expressed more concern about the financial wellbeing of others than men did ( Prichard and Christman, 2020 ). Survey data from eight countries indicated that women were more likely than men to perceive COVID-19 as a very serious health problem, to agree with restraining public policy measures, and to comply with them ( Galasso et al, 2020 ).…”
Section: Psychobehavioral Sex Differencesmentioning
confidence: 99%